A Study on Environmental Sustainability Practices among Students and Staff in International Islamic University Malaysia (IIUM) - Ninunroihan Jehtae; Arita Hanim Awang; Noraini Ahmad (Research Synergy Foundation, 2021)
This study is conducted to assess awareness and engagement on campus environmental sustainability initiatives among the students and staff of International Islamic University Malaysia (IIUM). In this research, a quantitative method was employed and a total of 100 survey questionnaires were randomly distributed to respondents. Based on the survey, 90.7% of the respondents are aware of the term